Developing the interface and functionality of gamified quiz platform - Muhamad, Marlina; Hussin, Hanani; Ibrahim, Shamsinar; Jamaludin, Mohd Fazil; Idrus, Nurul Izzati; Shuib, Nurfaznim (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In recent years, digital learning tools have become essential in education. Static quiz platforms are utilized due to its ease of use, automated grading, and structured assessments. However, this platform often lacks interactivity and engagement, leading to passive learning experiences where students simply complete quizzes. In contrast, gamified quiz platforms introduce elements such as real-time feedback, leaderboards, points, and time-based challenges, making learning more engaging. The project aims to analyze and compare the features of gamified and static quiz platforms, providing insights for educators on how to optimize digital assessment tools for better teaching and learning outcomes. Using a non-experimental approach, data was collected through observation and document analysis. The features of static platform were described and compared with gamification elements, focusing on the interface and functionality of those platforms. Based on the developed gamified quiz platform, the findings revealed several key differences in their design, functionality, and user engagement potential. Future research should examine how long-term use of gamified platforms affects student motivation and retention compared to static platforms. Conducting longitudinal studies could provide deeper insights into the sustained impact of gamification on learning outcomes.